PARENTAL INVOLVEMENT IN ONLINE LEARNING AND STUDENT LEARNING PERFORMANCE - Yosef Moan Banda; Maria Kristina Ota (Program Studi PGSD Universitas Flores, 2024)
Changes in the world of technology impact the world of education, and its development is very rapid daily. The problem that arises from online learning is miscommunication between schools, parents, and students. This research aims to determine parental involvement in online learning and the learning performance of class XI students at SMAK Syuradikara, Ende. The type of research used is quantitative descriptive, with the instrument being a questionnaire. Research data was obtained and analyzed using the SSPS software application, while data analysis was used using multiple regression. The results of this research indicate that there is a direct relationship between parental involvement in online learning and student learning performance. This can be shown by the calculated t value of 2.734, which is greater than the t table of 1.69092, with a degree of confidence or alpha of 1% and a df of 34. Another result is a moderate relationship between parental involvement in online learning and performance. Student learning is shown by an R-value of 0.425. Parental participation in online learning plays an essential role in student learning performance.